Multiple Metastases of a Transmissible Venereal Tumor in a Dog - Faccini, Leonardo Schuler; Legramanti, Wilson Maccarini; de Castro, Lucas Teixeira; Barreto Coelho, Ana Carolina; Caetano Teixeira, Mariana; Shild, Ana Lucia; Pereira, Clairton Marcolongo (Acta Scientiae Veterinariae, 2019)
Background: Transmissible venereal tumor (TVT) is a common contagious neoplasm in dogs that spreads through coitus. Extra-genital presentations of this tumor are frequent and usually develop through implantation of neoplastic cells on exposed mucosae. TVT metastasis is rare, and when it happens it’s usually affecting regional lymph nodes and adjacent cutaneous tissue. Case: A female mixed breed dog, with estimated age of 7 to 11-month-old, was rescued from the streets and taken to a veterinary clinic in the city of Porto Alegre, RS. The animal had multiple nodules on its body, vulva, ocular mucosa, and gingiva, along with signs of malnutrition and apathy. Cytological examination of the nodules and vulva was done and yielded a cytologic picture compatible with TVT. Weakly treatment with 0.3 mg/m² vincristine sulphate was used until clinical cure was noted. Approximately two weeks after clinical cure, the dog showed a blue colored eye and was referred for ophthalmological, where it was diagnosed with vision loss due to glaucoma secondary to a neoplasm. The eye was then removed and sent for histopathological evaluation. Histopathology of the eye was compatible with TVT diagnosis. One month after enucleation the animal display dispenia, pain, aggressiveness and epistaxis. The animal was euthanized and submitted for post-mortem evaluation. At necropsy there was a well-defined grayish-white, nodule near the thalamus. Similar nodules were also found on the lung, and anterior chamber of the eye. Histologically, all the nodules were compatible with TVT. Immunohistochemical examination was done, with the neoplastic cells being positive for vimentin and negative for cytokeratin, CD79a, CD3 and CD117. Based on the post-mortem examination and clinical history, diagnosis of TVT was given. Discussion: The clinical manifestation of the tumor in the genitalia presented by the animal is characteristic of TVT, but the extragenital presentation is less common. Although extragenital manifestations are well reported, most are due to auto-implantation (contact with the dog’s own genitalia) or hetero-implantation (contact with the genitalia of another dog). Metastases originating from the genitalia are markedly less common (5% of cases), and when they occur, they usually affect regional lymph nodes due to lymphatic communication. However, they can also occur in other organs, such as the liver, kidneys, spleen, tonsils, skin and subcutaneous tissue, bone, CNS, mesentery, and eyes. In this case, it is difficult to determine if the ocular tumor reported was due to metastasis or implantation by direct eye contact with TVT cells, since the animal lived on the street, and it was not possible to establish a more accurate history. The dog in this study was treated with vincristine sulfate; however, the treatment was stopped after one month, when no signs of the tumor were observed. Treatment with vincristine is the method of choice for TVT, since it is highly effective. However, rare cases of recurrence after treatment may occur. In addition, this drug does not cross the blood-brain barrier, and this may have favored the rapid reappearance of the tumor after treatment. The metastases from TVT to the CNS are extremely rare, with only a few cases reported in the literature. However, the possibility of metastases in animals with neurological and historical signs of TVT should be considered in the diagnosis. This case draws attention to the occurrence of TVT in the CNS of dogs with ocular TVT.